Initiation of encephalomyocarditis virus RNA translation: the authentic initiation site is not selected by a scanning mechanism. - Kaminski, A (1990)
The authentic initiation site on encephalomyocarditis virus (strain R) RNA is the 11th AUG codon (at nt. 834) from the 5' end of the viral RNA, the downstream of the two AUGs in the sequence....ACGAUGAUAAUAUGGCC... In order to assess the role of ribosome scanning in the selection of the correct initiation site, transcripts of a construct comprising the viral 5' noncoding sequence fused to a reporter gene were translated in vitro and the relative frequency of initiation at these two AUG codons, AUG-10 and AUG-11, was assayed. When deletions from the 5' end were made that retained less than 100 nucleotides of the viral 5'-noncoding sequence, initiation was highly cap-dependent and AUG-10 was utilized in preference to AUG-11, consistent with the scanning ribosome model. On the other hand, when the constructs included the entire 574 nt. segment of the 5' noncoding region situated between the poly(C) tract of the virion RNA and nt. 834, initiation was cap-independent and occurred exclusively at AUG-11, with negligible use of AUG-10. These results suggest that structural features of the 574 nucleotide segment cause initiating ribosomes to bind directly to AUG-11, without scanning the immediate upstream sequences that include AUG-10.